Pengaruh fee audit, rotasi auditor, reputasi KAP, audit delay terhadap kualitas audit - Marantika Sitompul, Sonya; Panjaitan, Melisa; Anggeresia Ginting, Wenny (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study was to determine the effect of audit fees, auditor rotation, KAP reputation, and audit delay on audit quality. The unit of analysis is property, real estate, and construction companies listed on the Indonesia Stock Exchange in 2017-2019. The data used by the researcher was obtained from financial report data. The population is property, real estate, and construction companies on the IDX. In taking the sample using purposive sampling technique, and obtained a number of 22 companies multiplied by three years of the research period. The data analysis used is descriptive using SPSS version 23. The results show that simultaneously audit fees, auditor rotation, KAP reputation, and audit delay do not affect audit quality. For further research, it is hoped that researchers will add years of observation. Â